Rapid Scan Cyclic Voltammetry (RSCV) investigation of oxygen reduction reaction (ORR) on gold ultramicroelectrode (UME): a novel methodology to study kinetics of formation of transient intermediates - Sharon Benny Alex; Linsha Vazhayal; Santosh K. Haram (Discover Electrochemistry)
Abstract This study employs Rapid Scan Cyclic Voltammetry (RSCV) with a gold ultramicroelectrode (Au UME) to investigate transient species in the oxygen reduction reaction (ORR) under alkaline conditions. Gold was purposefully chosen as the electrode material due to its ability to generate peroxide radicals via a two-electron transfer mechanism. RSCV on Au UME shows cathodic peaks, C1 and C2, linked to the sequential reduction of oxygen to peroxide anion and then to hydroxyl anion, and along with an anodic peak, A1, corresponding to peroxide anion oxidation back to oxygen. Quantitative analysis of these peaks, performed by integrating the peak areas, enabled rate determination for the formation of transient species. Thermodynamic and kinetic analyses further show a preference for decomposition over reduction, attributed to lower activation energy requirements. These findings demonstrate RSCV-UME’s effectiveness for real-time ORR intermediate detection and highlight how scan rate adjustments can alter reaction pathways, offering a powerful approach for exploring electrochemical mechanisms relevant to electrocatalysis and energy conversion technologies.